Developmental Dysphasia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The neuropatho1ogica1 findings in a seven year old girl with developmental dysphasia who died of complications of infectious mononucleosis are reported from the Departments of Neurology and Pediatrics and the Department of Pathology, Medical College of Georgia, Augusta, GA.